Obsidian exchange networks and highland-lowland interaction in the Lesser Caucasus Borderlands - Erb-Satullo, Nathaniel L.; Rutter, Matilda; Frahm, Ellery; Jachvliani, Dimitri; Albert, Paul G.; Smith, Victoria C. (Elsevier, 2023)
Obsidian sourcing studies have a long history in the Near East, but relatively few have focused on obsidian exchange after the Early Bronze Age. Here, we present a multi-technique analysis of an assemblage of 111 obsidian artifacts from excavated Late Bronze and Early Iron Age (LBA-EIA; c. 15th-6th c BCE) contexts at Mtsvane Gora, southern Georgia. Because the site is situated in the lowland Kura Valley and the nearest obsidian sources are in the highlands to the south and west, obsidian provenance can serve as a proxy for mapping highland-lowland interactions. Chemical compositions analyzed via portable X-ray fluorescence spectrometry (pXRF), electron microprobe analysis (EMPA), and laser ablation inductively-coupled plasma mass spectrometry (LA-ICP-MS), were compared with existing geological datasets of chemical analyses to identify the source of all but one of the artifacts analyzed. The results show that Chikiani, a source in the highlands of southern Georgia, was the geological origin of >90% of the objects analyzed. While acknowledging that obsidian exchange is just one aspect of highland-lowland interaction, this finding implies that Mtsvane Gora’s connections with the adjacent highlands were skewed towards greater engagement with some highland areas relative to others. More generally, the research suggests that geographic adjacency of highlands and lowlands does not necessarily mean that they were highly interconnected.
Keywords: Provenance; pXRF; Electron microprobe; LA-ICP-MS; Late Bronze Age; Early Iron Age